2016
DOI: 10.1186/s12906-016-1121-1
|View full text |Cite
|
Sign up to set email alerts
|

Amomum cardamomum L. ethyl acetate fraction protects against carbon tetrachloride-induced liver injury via an antioxidant mechanism in rats

Abstract: BackgroundMedicinal herb-derived drug development has become important in the relief of liver pathology. Amomun cardamomum is traditionally used therapeutically in Korea to treat various human ailments including dyspepsia, hiccupping, and vomiting. We investigated to assess the protective effect of A. cardamomum on carbon tetrachloride (CCl4)-induced liver damage through antioxidant activity in hepatic tissues of Sprague–Dawley rats.MethodsAntioxidant properties of different fractions from A. cardamomum from e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…This would greatly reduce lipid peroxidation injury and prevent a strong inflammatory response ( 22 ). Various antioxidant enzymes with high endogenous expression in the liver, such as SOD and GSH, are the major defense mechanisms against reactive oxygen species ( 23 ). Current results show that consumption of goats’ milk significantly elevated the activity of SOD and GSH in CCl 4 -damaged livers, indicating the ability of goats’ milk to restore and preserve the activity of these two enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…This would greatly reduce lipid peroxidation injury and prevent a strong inflammatory response ( 22 ). Various antioxidant enzymes with high endogenous expression in the liver, such as SOD and GSH, are the major defense mechanisms against reactive oxygen species ( 23 ). Current results show that consumption of goats’ milk significantly elevated the activity of SOD and GSH in CCl 4 -damaged livers, indicating the ability of goats’ milk to restore and preserve the activity of these two enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…The isoform CYP2E1 has been demonstrated to be largely responsible for this metabolic activation [ 12 , 13 , 16 ] and many studies have demonstrated that CCl 4 -induced hepatotoxicity can be potentiated or inhibited by substances that induce or inhibit CYP2E1 expression [ 44 , 45 , 46 , 47 ]. Interestingly, substances that inhibit CYP2E1 may protect cells against CCl 4 -toxicity [ 41 , 48 ]. In support of these observations in our study, we investigated whether the cyto-protective effect of EaF10 is related to the modulation of CYP2E1 expression through western blot analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Many herbs exhibit anti-inflammatory and anti-oxidative capacity, and are being used as adjunctive therapy for liver injury. Some compounds extracted from traditional Chinese medicine herbs possess anti-inflammatory and antioxidants effects against CCl 4 -induced oxidative stress, such as cardamomum, esculentoside A, Ocimum gratissimum, resveratrol, and quercetin (14)(15)(16)(17)(18). Among these herbs, Radix bupleuri is one of the most commonly used for many diseases such as viral hepatitis and chronic hepatic inflammation (19).…”
Section: Saikosaponin-d Alleviates Carbon-tetrachloride Induced Acutementioning
confidence: 99%